IMPLEMENTASI INTERNET OF THINGS (IOT) UNTUK MENDETEKSI KEBAKARAN RUANGAN - Nurlaela, Fitri (Lembaga Pengembangan Kinerja Dosen, 2025)
The Internet of Things (IoT) is used as information from advanced services by connecting objects physically and virtually. In the design of the detector application by utilizing the internet of things using Esp8266 MCU Node that will be connected to several sensors namely fire sensor (flame detector) to detect the presence of fire or light of fire, smoke or gas. sensor (MQ-2) to detect smoke or gas and a temperature sensor (DHT11) used to detect temperature and humidity. Relays as connectors to water spray machines, buzzers and blynk apps are used as controllers in providing notifications on Android. The fire detector can run in the event of a fire i.e. if the smoke detector detects smoke with a level of 800ppm followed by a buzzer that sounds, then the blynk app will also show a “TERDETEKSI ASAP” notification periodically then staff will press. an “OK” button on the notification if no smoke is detected and the buzzer will stop sounding The Temperature Sensor (DHT11) to monitor temperature and humidity periodically in the blynk app. The fire sensor (fire detector) detects a yellow fire light followed by a buzzer that sounds, then the blynk app will also show an “ADA API” notification periodically then staff will press the “ON” button on the button in the blynk app to activate the water machine until the water comes out to put out the fire. The buzzer will continue to sound and notifications will continue to appear until the fire is lit and will stop if it is not detected. If a fire is not detected, the buzzer will automatically stop sounding then staff will press the “OFF” button to turn off the water and staff will press the “OK” button on the notification.